The Son of Man and the Angel of the Lord Daniel 7.13-14 and Israel's Angel Traditions - Munoa, Phillip B. (2018)
Interpreters wrestle with Dan. 7.13-14 and its account of the 'one like a human being', traditionally known as 'the Son of Man'. This figure is subject to two competing interpretations: symbol (suffering Jews) and individual (Michael). These positions draw upon Daniel 7's interpretation and Daniel's later chapters, but interpreters need to consider the Hebrew Bible's angel of the Lord tradition and more fully engage Dan. 7.13-14, the angelic interests of Daniel 2-6, the later Additions to Daniel, and Second Temple interpretations of Daniel 7. These materials are consistent with this angel's portrayal in the Hebrew Bible and indicate a growing interest in this angel's saving intervention on behalf of Israel. When Dan. 7.13-14 is read in light of this angelic tradition, a long-overlooked reading that argues for an angel of the Lord merits serious consideration.
Keywords: Bibel; 1 Enoch; 2 Maccabees; Additions to Daniel; Angel of the Lord; Daniel; Son of Man; Angel